Creating Websites: Principles, Technologies, and Best Practices (Multidisciplinary Journal of Science and Technology, 2025)
In the digital age, websites serve as essential platforms for communication, business, education, and personal expression. This article explores the fundamental process of creating websites, covering design principles, development technologies, and deployment strategies. We analyze the roles of front-end and back-end technologies, responsive design, user experience (UX), and web hosting. The article also discusses modern trends like no-code platforms, content management systems (CMS), and progressive web applications (PWA). Understanding website development empowers individuals and organizations to effectively establish an online presence